Pelatihan presentasi menggunakan Microsoft Power Point pada SMP Patra Mandiri 2 Palembang - Rasmila Rasmila; Nurul Huda; Jemakmun Jemakmun; Aan Restu Mukti; Rahayu Amalia; Novri Hadinata; Kurniawan Kurniawan; Ade Putra; Christin Evasari Nainggolan (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2022)
Learning media is a tool used by teachers to convey subject matter to students or media used by students to deliver assignments given by the teacher. In this training activity, computer-based learning media were introduced for presentations using Microsoft PowerPoint, which students of SMP Patra Mandiri 2 Palembang could use to present assignments given by the teacher to the front of the class with attractive shapes and appearances. Community Service Activities (PKM) in the form of training are carried out for two days, in which students are required to be able to make presentation materials using Microsoft PowerPoint and present the material they made in front of the computer laboratory room. This activity is carried out in direct and interactive practice, where students directly practice the material provided by the PKM Team, and students can also have direct discussions with the PKM Team. Before implementing the training activities, students were given a written knowledge test to determine the level of students' understanding of the training material to be delivered. Only 20% of the student participants often made materials using Microsoft PowerPoint. After two days of implementing this training activity, an evaluation was carried out regarding the knowledge and abilities of the student participants in creating and presenting material using Microsoft PowerPoint. From the evaluation results, it can be seen that all student participants have succeeded in making presentation materials using Microsoft PowerPoint and some student participants are also able to present the material in front of the class